Over-expression of JAZF1 promotes cardiac microvascular endothelial cell proliferation and angiogenesis via activation of the Akt signaling pathway in rats with myocardial ischemia-reperfusion. Issue 14 (18th July 2019) - Shang, Jie; Gao, Zhi-Yong; Zhang, Li-Yan; Wang, Chun-Yu
ABSTRACT: Myocardial ischemia-reperfusion (I/R) injury is caused by endothelial dysfunction and enhanced oxidative stress. The overexpression of JAZF1, a zinc finger protein, has been reported to promote cell proliferation and suppress myogenic differentiation in type 2 diabetes. However, the involvement of JAZF1 in myocardial I/R injury remains to be unclear. The current study aims to investigate the role by which JAZF1 influences cardiac microvascular endothelial cells (CMECs) in a rat model of myocardial I/R injury. A total of 50 rats were established as a myocardial I/R model to isolate CMECs, with alterations in JAZF1 expression. After that, the gain- or loss-function of JAZF1 on the proliferation, apoptosis and tube formation ability of CMECs were evaluated by a series of in vitro experiments. Results indicated that JAZF1 was down-regulated in CMECs of rats with myocardial I/R injury. After treatment with JAZF1, the levels of VEGF, Bcl-2, PDGF and p-Akt/Akt were all increased; however, the expression of Bax, caspase-3, caspase-9, p-Bad/Bad, c-caspase-3/caspase-3, c-caspase-9/caspase-9, and p-FKHR/FKHR exhibited decreased levels; CMEC proliferation and angiogenesis were increased, while cell apoptosis was attenuated. CMECs transfected with JAZF1 shRNA exhibited the contrary tendencies. The key findings of this study suggest that the over-expression of JAZF1 alleviates myocardial I/R injury by enhancing proliferation and angiogenesis of CMECs and in turn inhibiting apoptosis of CMECs via the activation of the Akt signaling pathway.